Evaluation of the Technical Condition and Efficiency Indicators of the Stone Crusher (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
We use important crushing machines in several industries to reduce particle size using rock crushers. Nowadays, higher education institutions of the Republic of Uzbekistan in laboratories and research centers, as well as mining and construction used in networks. For crushing stones with raw materials and manual labor to meet various requirements in the Republic of Uzbekistan focusing on the use of stone crusher devices, ignoring the risks associated with sectors. Technological grinders are designed with a hammer mill it will be necessary to consider standard design requirements, local content and cost. Power required for crushing. Based on research, it is determined that granite is 4.5-6 kW with a required throughput of 500 kg/h. In basic studies, rock hardness, mechanical properties for material selection, material properties (anisotropic and isotropic), production requirements and the cost should be calculated. Grinding devices was tested and the actual capacity was 400 kg/h with a transfer efficiency of 65%. This the gradation coefficient of crushed rocks was found to be 3.73. A number of information are provided to improve the efficiency of shredder devices.